Populism and fascism in Europe: case of Romania - Iryna Kiyanka; Nadiya Levytska (Language, Culture, Politics)
The article focuses on the essence of populism and fascism in the context of the political regime in Romania. It analyses the real threat of fascism in the interwar period in Romania as well as a negative impact on the socio-economic sphere in the Romanian society. The article also points to the fact that the fascist party in Romania was short-lived. The dictatorship of Ion Antonesku and his followers, in fact, implemented some points of their program (eg, anti-Semitic activities), adopting mate nationalistic and conservative ideology, but it did not accept the fascist "revolutionary" ideas and totalitarian structures. Populism is a good option for election campaigns. After all, people always like a simple and understandable way without undue burden. Human logic and speculation aid such a way. Nevertheless, populism is a nourishment for authoritarian leaders.